Five smooth stones for pastoral work - Peterson, Eugene H. 1932- (Grand Rapids, MI Eerdmans, 1989)
Includes bibliographcial references.
Originally published : Atlanta, GA : J. Knox, 1980, which see also.
Keywords: Pastoral theology; Bible. O.T. Five scrolls -- use; Bible. O.T. Five scrolls -- criticism, interpretation, etc